Caught in Confucius’ Shadow the Struggle for Women’s Legal Equality in South Korea - Cho, Erin (Columbia Journal of Asian Law, 1998)
Historian Martina Deuchler has said that no other nation in the world was as transformed by Confucianism as Korea. When the Chos6n Dynasty (1392-1910) adopted Neo-Confucianism as its ruling ideology, Korean society came to consider “Confucianization” to be synonymous with civilization. By the late seventeenth century, Confucianism restructured family organization, marriage and kinship practices, and established strict gender roles between men and women. While Confucianism has not existed as a formal state ideology in Korea since 1910, people continue to adhere to Confucian norms in their daily lives. Arranged marriages, ancestor worship, respect for elders, filial piety, and the subordination of women remain deeply ingrained in the private personas of the Korean people. The incorporation of Confucian patriarchal and patrilineal principles into the family law Korea adopted in 1958 reflects the resilience of Confucianism in shaping Korean social thought and behavior.